Introduction - Carlos O. Maidana (2018)
© 2014, The Author(s). Liquid alloy systems have a high degree of thermal conductivity far superior to ordinary non-metallic liquids. This results in their use for specific heat conducting and dissipation applications. For example, liquid metal-cooled reactors are both moderated and cooled by a liquid metal solution. These reactors are typically very compact and can be used in space propulsion systems and in fission reactors for planetary exploration. Thermo-magnetic systems, such as electromagnetic pumps and electromagnetic flow meters, exploit the fact that liquid metals are conducting fluids capable of carrying currents source of electromagnetic fields useful for pumping and diagnostics. But the coupling between the electromagnetics and thermo-fluid mechanical phenomena gives rise to complex engineering and numerical problems. The environment of operation adds even further complexities with high temperature gradients, radiation and vacuum. This chapter gives an overview of the booklet content, its motivations, describe current and future work and acknowledge people and institutions that without their collaboration this work would not have been possible.